ICoLLT 4.0 2024 marks milestone in learning and teaching of languages - Asiah, Kassim (UMPSA, 2024)
KUALA LUMPUR, 20 May 2024 – In a momentous convergence of global minds, the International Conference on Language Learning and Teaching 2024 (ICoLLT 4.0), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) opened with resounding aims, heralding a new realm of teaching and learning of languages.